Extensive Rehabilitation of a Medically Compromised Patient with Vitamin-D Deficiency Using Dental Implants: A Case Report - Parakh, Mayank Kumar; Shetty, Manoj; Hegde, Rakshith; Shetty, Athma (Journal of Health and Allied Sciences NU, 2023)
Patients often report to dental practice with a wide range of chief complaints. At times, young adult patients, seemingly fit clinically, report extensively damaged dentition. It is important that such patients be evaluated more extensively and the etiology if any, for such debilitated dentition, must be assessed. Dental implants are a successful treatment modality that helps to restore the function and esthetics of a patient. Early dental implant failure refers to the dental implant's failure to osseointegrate with the native bone during the phase of healing. This article describes one such young adult patient of 34 years, who presented with a history of dental implant failures without any underlying systemic comorbidities. The patient's elaborate history was taken and it was found that the patient had a severe vitamin D deficiency. Following treatment of the deficiency, the case was managed effectively with the help of a maxillary cement-retained implant-supported full-arch fixed prosthesis and, an implant and tooth-supported mandibular cast partial denture.
Keywords: dental implants; vitamin D; rehabilitation; cast partial denture; fixed prosthesis